EVALUASI PELAKSANAAN PROGRAM PENGEMBANGAN KABUPATEN/ KOTA LAYAK ANAK DI KABUPATEN BENGKALIS (STUDI KASUS: ANAK BERHADAPAN DENGAN HUKUM) - Arniana "; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Bengkalis District implemented a policy in the form of a mandate program from the Ministry of Women Empowerment and Child Protection namely Development of District/ City Worthy of Children. But the implementation of this program is in fact still many shortcomings in the implementation. The purpose of the issues is to evaluatate the implementation of the Program Development of District/ City Worthy of Children in Bengkalis District, especially for children face with the law, any factors that affect Evaluation Implementation of the program District/ City Worthy of Children in Bengkalis, especially children face with the law.There are 6 evaluation criteria namely effectiveness, efficiency, adequacy, equity, responsiveness, and determination. In this study, the researcher uses the informant research through key informants and complementary informants. Key informants are the Secretary of the integrated service center of women and children empowerment, while complementary informants are figures who are considered to know about this problem. For that information researchers used the technique of snowball sampling.Based on the results of the evaluation of the researchers that the evaluation of development programs District/ City Worthy of Children in Bengkalis District (Case Study: Children Faced With the Law) has not optimally. Implementation has not been effective, inefficient because in terms of cost, and energy that is still lacking, not enough to satisfy the needs of the society, the response to this policy is also lacking. The factors that influence the evaluation of this policy are Sosialization, Facility, Society Participation, and communication among organization.Keywords: Policy, Evaluation, District / City Worthy of Children